Pengaruh Job Insecurity, Psychological Distress, Persepsi Career Growth Opportunities, dan Reward Terhadap Motivasi Kerja Karyawan pada PT Global Digital Niaga (Blibli) - M Fauzan; Maman Suratman (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
The rapid growth of the e-commerce sector in Indonesia requires high adaptability from human resources, often accompanied by work pressure and uncertainty. This research aims to analyze the influence of job insecurity, psychological distress, perceived career growth opportunities, and rewards on employee work motivation at PT Global Digital Niaga (Blibli). Work motivation is a crucial factor for organizational success in facing competitive digital industry challenges. The research method used is quantitative with descriptive and verificative approaches. Data was collected through questionnaires and analyzed using statistical techniques to test relationships between variables. This study involved 100 permanent employees as respondents to provide an objective representation of the company's conditions. The results indicate that perceived career growth opportunities and rewards have a positive and significant effect on work motivation. However, job insecurity and psychological distress do not show a significant influence on employee work motivation. Simultaneously, these four variables explain 63.7% of the variation in work motivation. In conclusion, strengthening career development programs and fair reward systems are the primary strategies to enhance employee motivation.